Applications of thermal imaging camera for assessing structural integrity - Tantele, Elia; Votsis, Renos; Kyriakides, Christopher (My University, 2018)
© 2018 SPIE. The ongoing degradation of structures is associated with expensive maintenance and the resulting decline in safety, force the engineer to search for structural health monitoring tools that will be fast, effective, cover large areas and cost as minimum as possible. In this context the thermal imaging cameras are an ideal monitoring tool; with the radical development of higher resolution thermal imaging, the decreasing cost of the camera and its portable size makes this technology promising to accomplish the requirements of modern structural monitoring. Thermal imaging camera uses algorithms to interpret visual displays of the amount of infrared energy emitted, transmitted and reflected by an object and form images that are invisible to the human eye. Therefore, the thermal imaging technology can be used as a tool to help the engineer gain better insight and viable information and thus enabling the structure to retain/sustain its function, form and strength within acceptable limits under operational loading. This paper presents applications of this technology for assessing the integrity of structures along with possible trends and gains on different areas of structural integrity, such as the detection of corrosion in steel rebars embedded in RC structures and the chloride contents on concrete surface.
Keywords: Monitoring; Remote Sensing; Structural Integrity; Thermal Imaging Camera